Re-appraising the influence of location advantages in the political risk and foreign direct investment relationship: A conception - Koko, Musa Hatim; Yatiban, Aminurraasyid; Zengeni, Knocks Tapiwa (Society of Scientific Research and Education (SSRE), 2016)
This paper takes a conceptual step to analyze the link between Foreign Direct Investment (FDI) and political risk by extending to include location and its potential advantages as possible risk mitigating factors earlier neglected by international investors and international business scholars.Where location factors are beneficial they are expected to override the mounting political risks as the best risk hedging mechanism. We re-appraised this relationship by supporting the existing literature on location dynamics, its determinants and decisions on international investment.The paper further contribute to literature by supporting the clamor for moving away from region or country analysis to within country assessment in order to favor available location benefits considered crucial in mitigating political risk.The growing relevance of within country analysis can lead to finding how best to minimize political risk impact on FDI inflow.